A BIBLIOMETRIC ANALYSIS OF BEHAVIOURAL FINANCE: INVESTOR SENTIMENTS - Satpal; Reetu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study presents a comprehensive bibliometric analysis of research on investor sentiment using the Scopus database. The dataset includes publications from 1994 to 2023, focusing on "investor sentiment" and related terms across subject areas such as finance, economics, management sociology etc. The analysis was conducted using VOSViewer software to visualize trends in academic publishing, co-authorship networks, and citation patterns. Our findings indicate a growing interest in the influence of investor sentiment on financial markets, with a notable rise in publications in the past decade. Key research themes identified include behavioral finance, the impact of sentiment on asset pricing, and the role of investor psychology in market volatility. The analysis also highlights key authors, influential papers, emerging sources etc. This bibliometric study contributes to a deeper understanding of the intellectual structure and evolution of the investor sentiment research field, providing valuable insights for academics, policymakers, and market participants.